ANALISIS FAKTOR-FAKTOR PENYEBAB KREDIT MACET DI KOTA PONTIANAK (KAJIAN KREDIT KUPEDA PADA PT. BANK KALBAR) - Oktarizka, feie Puja (Jurnal Pembangunan dan Pemerataan, 2012)
This study entitled "Analysis of Factors Contributing to Bad Debts In the city of Pontianak '. The problems studied in this paper is what factors lead to bad loans in Pontianak (Credit Assessment Kupeda At PT. Bank Main Branch West Kalimantan). The purpose of this study was to determine the factors that led to bad loans, especially credit Kupeda at PT. Kalbar Bank branch in New York City and efforts in dealing with bad loans kupeda at PT. Bank Branch Pontianak Kalimantan. In this study the authors use a survey method of research method is the data collected through questionnaires or structured questionnaires. Data sources used were obtained from the data object is supported by research and questionnaires. The results of data analysis showed that factors that lead to bad credit credit Kupeda especially in PT. Bank Kalbar declining economic conditions do not favor the debtor, the debtor that caused the unfortunate debtor does not timely pay and loan repayments allow a risk of collectibility or bad loans, the company's internal problems and the debtor, the debtor escaped or run away causing delays payment debtor in bank liabilities, the debtor is not timely in the repayment of credit and installment amounts not in accordance with the obligations. Should PT. Bank Kalbar before giving credit Kupeda must first analyze in order to avoid bad credit and credit must carefully take into account the ways of the solution set. Key words: Bad credit